Effects of climate change on grain yield in a major grain producing area of China - Xinhe Huang; Yanping Cao; Mengyang Cui; Qingqing Li (Scientia Agricola, 2025)
ABSTRACT The impact of climate change on food production is evident across most regions of the world, including China, particularly in the Huang-Huai-Hai Plain (HHHP), which is crucial for grain production. Investigating the quantitative effects of climate variables on grain yield is therefore of paramount importance. A study of the HHHP region revealed an upward trend in temperature, along with a downward trend in shortwave radiation and precipitation from 1995 to 2018. During this period, the grain yield exhibited two distinct stages: a decline from 1.1 billion tons in 1995 to 0.96 billion tons in 2003, followed by a period of stable growth from 1 billion tons in 2004 to 1.5 billion tons in 2018. In terms of spatial dynamics, the grain yield in the HHHP transitioned from a pattern of scattered high-yield cities to concentrated high-yield areas. From a single-factor perspective, temperature (q = 0.44) exhibited the most significant impact to grain yield in the HHHP, followed by shortwave radiation (q = 0.28) and precipitation (q = 0.24). The interaction between temperature and precipitation was identified as the primary driver of grain yield in the HHHP and its sub-region, Hebei Province. In contrast, in Henan and Shandong Provinces, the predominant influence was attributed to the interaction of shortwave radiation and temperature. The sensitivity degree model indicates that 87.5 % of cities within the HHHP region are sensitive to cropland with respect to grain yield. The present study demonstrates the multifaceted impacts of climate change on grain yield and provides essential evidence for developing effective strategies to ensure global food security.